INVESTIGATION OF THE FORMATION OF SPELEOTHEMS IN THE AGIOS GEORGIOS CAVE, KILKIS (N. GREECE) - Antonelou, A.; Tsikouras, B.; Papoulis, D.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2010)
The Agios Georgios cave at Kilkis (North Greece) contains a large variety of speleothems and it is considered as one of the most decorated caves of Greece. For this study a coordinated geochemical and textural investigation of the speleothem was carried out. This stalactite was cut along its growth axis and a transverse slab of it shows parallel calcite layers of varying thickness and colour, whose regularity and spacing suggest an annual origin. Microscopic investigation of polished-thin sections resulted in a detailed description of several fabric types. Scanning Electron Microscopic study and microanalyses revealed that pure calcite is dominant; local Mg-bearing calcite occurs, too. In some pores among the faceted crystals there is a variety of clay minerals that, along with the development of Mg-bearing calcite, are interpreted as the result of microbiological or/and climatic changes. Numerous changes in environmental conditions in caves (particularly changes in water flow rates) cause variations in the degree of perfection of crystallite lateral growth and inclusions may trapped by their advancing growth surface. The speleothem is studied in order to generate archives of climate change (aridity, flow rates etc.) and indentifying shifts in climate system. The successive laminae in the studied speleothem from Agios Georgios suggest alternative cool and warm periods in the past climatic conditions of northern Greece.